Adolescents with atopic disorders have an attenuated cortisol response to laboratory stress - Wamboldt, Marianne Z.; Laudenslager, Mark; Wamboldt, Frederick S.; Kelsay, Kim; Hewitt, John (Journal of allergy and clinical immunology, 2003)
Background: Patients with allergic disorders have been noted to have variations in cortisol patterns under natural conditions as well as a differential cortisol response to stress. Objective: The main goal of this study was to examine hypothalamic-pituitary-adrenal (HPA) axis differences in atopic adolescents. Methods: Subjects were a community sample of 202 adolescents (52% male; mean age, 16.2 years). Atopic status was determined by skin testing and clinical history. Saliva samples for cortisol assay were obtained 4 times during a “typical day” and at 4 time points during laboratory procedures. Results: One third of the sample (33%) had a clinical atopic disorder, primarily allergic rhinitis; 39% had positive skin test results without clinical symptoms; and 27% had no signs or symptoms of allergic disorders. There were no significant effects of atopic status on home cortisol patterns. Presence of clinical atopy was significantly (P < .05) associated with lower cortisol levels in response to laboratory stressors. Conclusions: Adolescents with a history of atopic illnesses had an attenuated cortisol response to the stress of laboratory procedures compared with adolescents with positive skin test results alone or nonatopic adolescents. An attenuated cortisol response to a stressor may help us understand the link between stress and exacerbation of atopic illness. (J Allergy Clin Immunol 2003;111:509-14.)